SOLIDARITAS SOSIAL DALAM BINGKAI KEIMANAN: INTERPRETASI HADIS PERSPEKTIF TEORI ROBERT PUTNAM - Putri, Avanda Chintya Cahyaning Putri; Jubaedi (Institut Agama Islam Negeri Kediri, 2025)
This study examines social solidarity in Islam, focusing on taʿāwun (mutual assistance) as articulated in the hadith and analyzed through Robert D. Putnam’s social capital theory. Contemporary Muslim societies face increasing individualism and weakening communal cohesion, while the practical application of the Prophet’s guidance on mutual help remains limited. Although previous studies have addressed Islamic social ethics and social capital separately, a gap persists in linking authentic hadith sources with systematic social science frameworks to explain community cohesion. This research employs a qualitative library-based methodology, drawing on primary data from canonical hadith collections, including Ṣaḥīḥ al-Bukhārī, Ṣaḥīḥ Muslim, and Sunan Abī Dāwūd, supported by relevant scholarly literature. Data analysis proceeded in three stages: textual analysis (ʿIlm al-Maʿānī al-Ḥadīth), intertextual thematic analysis, and contextual-social analysis using Putnam’s social capital framework. The findings reveal that hadiths on mutual assistance consistently embed key social capital elements, including trust (al-thiqah), reciprocity (al-muʿāwānah), norms (al-qawāʿid/al-aʿdāb), and networks (al-shabākāt/al-ʿalāqāt), within an ethical and spiritual framework, enhancing collective action, community resilience, and social cohesion. Unlike secular theories, Islamic social capital integrates moral and spiritual dimensions, providing a sustainable mechanism for enduring social solidarity. Conceptually, this study contributes by integrating Islamic teachings with social capital theory, offering a systematic analytical tool to understand the mechanisms of cohesion and sustainability in Muslim communities.